2017
DOI: 10.1002/1873-3468.12595
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing isomiR variants within the microRNA‐34/449 family

Abstract: miR‐34/449 microRNAs are conserved regulators of multiciliated cell differentiation. Here, we evidence and characterize expression of two isomiR variant sequences from the miR‐34/449 family in human airway epithelial cells. These isomiRs differ from their canonical counterparts miR‐34b and miR‐449c by one supplemental uridine at their 5′‐end, leading to a one‐base shift in their seed region. Overexpression of canonical miR‐34/449 or 5′‐isomiR‐34/449 induces distinct gene expression profiles and biological effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 54 publications
2
43
0
1
Order By: Relevance
“…It is known that miRNA genomic clusters are often co-transcribed as related miRNAs, which share the same seed region or belong to functionally related miRNA families. A typical example is given by the miR-34/449 superfamily, which exhibits extensive genomic redundancy by encompassing six homologous miRNAs (miR-34a, miR-34b/c and miR-449a/b/c) located on three distinct genomic loci (28). While the tumor suppressor role of miR-34 has been largely established, the effects of the miR-449 family members have not been addressed in human CRC, as well as CAC (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that miRNA genomic clusters are often co-transcribed as related miRNAs, which share the same seed region or belong to functionally related miRNA families. A typical example is given by the miR-34/449 superfamily, which exhibits extensive genomic redundancy by encompassing six homologous miRNAs (miR-34a, miR-34b/c and miR-449a/b/c) located on three distinct genomic loci (28). While the tumor suppressor role of miR-34 has been largely established, the effects of the miR-449 family members have not been addressed in human CRC, as well as CAC (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Moderate level of isomiR expression has been observed between Dicer-independent miRNA and non-dominant miRNA, suggesting complex miRNA maturation process at isomiR level [38]. The study performed by Mercey and colleagues [39] on human miR-34/449 family suggested that isomiR variants which differ by single canonical counterpart can share biological functions indicatind additional mechanism by which regulation of complex biological function can be perfectly and easily employed by miRNA machinery.…”
Section: Importance Of Isomirsmentioning
confidence: 99%
“…In general, 3 -isomiRs are more abundant than 5 -isomiRs, however, a number of microRNAs do have prevalent 5 -isomiRs [75][76][77][78]. Since a microRNA's 5 -end determines its seed sequence, 5 -isomiRs have an altered targetome compared to the canonical microRNA sequence and are thus functionally different ( Figure 2) [67,[79][80][81]. While 3 -isomiRs do not have an altered seed sequence, their 3 -end variability has been associated with altered microRNA stability and turnover [82][83][84][85][86].…”
Section: Isomirsmentioning
confidence: 99%